Falta de acceso a internet ante el derecho constitucional de la educación en tiempos de COVID-19. - Herrera Rodríguez, Liliana Paola (2023)
The purpose of this study is to establish the gap in access to education as a result of the Internet connection, due to various factors that made it impossible for children and adolescents around the world to have an adequate education during the pandemic. The digital teaching method has been imposed in a general way, which caused a digital divide for economic and technological reasons, as well as difficulties within families and educational centers.